PENGARUH PENELITIAN DAN PENGEMBANGAN SDM TERHADAP KINERJA PENGELOLAAN GEDUNG MELALUI PENDEKATAN BALANCED SCORECARD DENGAN ANALISIS SEM-PLS (STUDI KASUS: MENARA KANAYA) - Kezia Samosir; Ahmad; I Wayan Sukania (Jurnal Ilmiah Teknik Industri, 2025)
This study aims to evaluate the influence of Human Resource Research and Development (HR R&D) on the performance of building management at Menara Kanaya, Nuansa Cilangkap, using the Balanced Scorecard (BSC) approach and Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 215 respondents consisting of building managers, operational staff, and residents through questionnaires, field observations, and short interviews. The BSC assessment shows that the overall management performance is at a moderately good level, with the highest score in the Learning and Growth perspective (3.4), followed by Customer (3.0), Internal Process (2.9), and Financial (2.8). SEM-PLS analysis indicates that HR R&D has a significant positive effect on the Financial perspective (β = 0.896; p = 0.000) and Internal Process perspective (β = 0.479; p = 0.000), but does not significantly influence the Customer perspective. These findings highlight that training and development enhance operational efficiency and cost-effectiveness, yet the improvements are not directly perceived by residents. Overall, the study confirms that HR development plays a strategic role in improving building management performance and that the Balanced Scorecard serves as an effective framework for evaluating organizational performance in public service facilities.